2015
DOI: 10.15388/ekon.2014.93.5044
|View full text |Cite
|
Sign up to set email alerts
|

Disclosure on Intellectual Capital in Annual Reports of Nasdaq Omx Baltic-Listed Companies

Abstract: According to the current accounting standards, only a minor part of intellectual capital is presented in financial statements. Nevertheless, more and more companies in Lithuania and abroad reveal information about their intellectual capital in their annual statements. Therefore, the object of this paper is the disclosure of information on intellectual capital, and the aim is to reveal the trends of disclosure of information on intellectual capital based on annual reports by Nasdaq OMX Baltic-listed companies i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 26 publications
(15 reference statements)
0
6
0
Order By: Relevance
“…Many studies have reported an increase in disclosure over a period; however, overall low levels of ICD were found in Spain (Ordóñez de Pablos, 2003;Oliveras and Kasperskaya, 2008). Ramanauskaitė and Laginauskaitė (2014) reported an increase in disclosure in Baltic countries. In contrast, Ramanauskaite and Rudzioniene (2013) studied firms in Lithuania and found that the level of disclosure decreased over the period of study.…”
Section: Review Of Literature and Hypothesis Developmentmentioning
confidence: 98%
“…Many studies have reported an increase in disclosure over a period; however, overall low levels of ICD were found in Spain (Ordóñez de Pablos, 2003;Oliveras and Kasperskaya, 2008). Ramanauskaitė and Laginauskaitė (2014) reported an increase in disclosure in Baltic countries. In contrast, Ramanauskaite and Rudzioniene (2013) studied firms in Lithuania and found that the level of disclosure decreased over the period of study.…”
Section: Review Of Literature and Hypothesis Developmentmentioning
confidence: 98%
“…Abeysekera (2008) published similar results when comparing the level of disclosure in Sri Lanka and Singapore. Ramanauskaite and Laginauskaite (2014) revealed that Lithuanian companies are superior in disclosing IC information when compared to the Estonian and Latvian in annual reports of Nasdaq OMX Baltic-listed companies. Most recently, an investigation into Australian and Sir Lankan firms indicated that external structure disclosures were most common among Austrian firms, while intellectual property disclosures were more preferable by Sri Lankan larger firms (Pratheepkanth, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Another line of research transversally analyzes this type of disclosure, reviewing content by country, for example, Guthrie and Petty (2000) for Australian companies; Bontis (2002) for Canadian companies; Abeysekera and Guthrie (2005) for companies in developed countries compared with non-developed countries; An and Davey (2010), who provide evidence regarding the low level of IAD in a large number of Chinese listed companies that nevertheless exhibit a strong commitment in the manner in which they publicly disclose this information; Joshi et al (2012) for information technology companies in India and Australia; Ramanauskakité and Laginauskaité (2014) for the Baltic states of Lithuania and Estonia; Bianchi et al (2016) for France, Germany, Italy, and the UK; Catalfo and Wulf (2016) for Italy and Germany; Razak et al (2016) for Saudi Arabia; Wang et al (2016) for China and India; and finally, Pisano et al (2017) for European non-financial firms listed on the Italian, French and German stock exchanges.…”
Section: Intangible Asset Disclosures: State Of the Artmentioning
confidence: 99%
“…First, in relation to the pursued objectives, we must note that content analysis is used in all cases to understand the extent of the IAD activities performed by companies both at a specific time and throughout a period of no longer than three years (Vamdemaele et al , 2005; Castelo et al , 2010; Abdifatah and Mubaraq, 2012; De Silva et al , 2014; Ramanauskakité and Laginauskaité, 2014; Saitua et al , 2014; Ruiz-Rodríguez, 2016). This confirms the most commonly used technique to determine the amount of information disclosed regarding intangible assets but simultaneously demonstrates that the quality of such disclosures does not appear to be a research objective, thus presenting a future line of analysis, as presaged by Guthrie and Abeysekera (2006).…”
Section: Approaching Iad In Content Analysesmentioning
confidence: 99%
See 1 more Smart Citation